Phosphorus extractability in relation to soil properties in different fields of fruit orchards under similar ecological conditions of Pakistan - Bibi, Sumera; Irshad, Muhammad; Ullah, Farid; Mahmood, Qaisar; Shahzad, Muhammad; Tariq, Muhammad Atiq Ur Rehman; Hussain, Zahid; Mohiuddin, Muhammad; An, Ping; Ng, A. W. M.; Abbasi, Asim; Hina, Aiman; et al. (Frontiers in Ecology and Evolution, 2023)
Productivity of an orchard generally depends upon the fertility of the soil and the nutrient requirements of the fruit trees. Phosphorus (P) extractability from soils influences the P sorption, release patterns, and P bioavailability. A study was carried out to investigate P extractability via seven extraction methods in relation to soil properties in three fruit orchards. In total, 10 soil samples were collected from each fruit orchard, namely, citrus (Citrus sinensis L.), loquat (Eriobotrya japonica L.), and guava (Psidium guajava L.), located in similar ecological conditions to the Haripur district of Pakistan. Available P in the soil was extracted using deionized H2O, CaCl2, Mehlich 1, Bray 1, Olsen, HCl, and DTPA methods. Selected soil properties [pH, electrical conductivity (EC), soil organic matter (SOM)], texture, cation exchange capacity (CEC), macronutrients, and micronutrients were also determined. Soils sampled from orchards indicated significant differences in soil properties. Orchards have sequestered more amount of C stock in soil than without an orchard. The extractability of P from soils was profoundly affected by P extraction methods. The average amount of extractable P was relatively higher in those soils where the total amount of P was also higher. These methods extracted different pools of soil P with varying P concentrations regulated by the soil properties. Phosphorus amounts extracted were varied in the order of HCl > DTPA > Mehlich 1 > Bray 1 > Olsen > CaCl2 > water. Among orchards, a higher amount of P was found in soils of loquat followed by citrus and guava orchards. Regardless of the method, subsurface soil got a lower concentration of extractable P than surface soil in all orchards. The extractable P was highly associated with soil properties. DTPA extractable P was related to SOM soil clay content and CEC by R2 values of 0.83, 0.87, and 0.78, respectively. Most of the extraction methods were positively correlated with each other. This study indicated that SOM inputs and turnover associated with orchard trees exhibited a substantial quantity of extractable P in soils. Predicting available P in relation to its bioavailability using these methods in contrasting soils is required.